Implementing Differentiated Assessment in Islamic Religious Education to Enhance Students’ Critical Thinking in the Context of the Merdeka Curriculum at Senior High Schools - Nazhan, Faiz Aswa; Anwar, Saepul; Romli, Usup; Firmansyah, Mokh Iman; Muflih, Abdillah (Pascasarjana IAIN Kudus, 2025)
This study explores the experience of an Islamic education teacher in implementing differentiated assessments and analyzes their impact on students’ critical thinking development. A qualitative approach with a descriptive-analytical method was used to collect data through an in-depth interview with a PAI teacher at SMAN 7 Bandung, which was supported by relevant literature. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, display, and drawing conclusions. The results demonstrate that differentiated assessments provide students with opportunities to express their understanding in creative and reflective ways. This approach also promotes the development of Ennis’s five critical thinking indicators: clarification, basic support, inference, advanced argumentation, and self-regulation. The study concludes that differentiated assessment significantly enhances students’ critical thinking skills in Islamic religious education.